Vitamin D deficiency aggravates COVID-19: systematic review and meta-analysis - Pereira, Marcos; Dantas Damascena, Alialdo; Galvão Azevedo, Laylla Mirella; de Almeida Oliveira, Tarcio; da Mota Santana, Jerusa (Critical reviews in food science and nutrition, 2022)
There is still limited evidence regarding the influence of vitamin D in people with COVID-19. In this systematic review and meta-analysis, we analyze the association between vitamin D deficiency and COVID-19 severity, via an analysis of the prevalence of vitamin D deficiency and insufficiency in people with the disease. Five online databases-Embase, PubMed, Scopus, Web of Science, ScienceDirect and pre-print Medrevix were searched. The inclusion criteria were observational studies measuring serum vitamin D in adult and elderly subjects with COVID-19. The main outcome was the prevalence of vitamin D deficiency in severe cases of COVID-19. We carried out a meta-analysis with random effect measures. We identified 1542 articles and selected 27. Vitamin D deficiency was not associated with a higher chance of infection by COVID-19 (OR = 1.35; 95% CI = 0.80-1.88), but we identified that severe cases of COVID-19 present 64% (OR = 1.64; 95% CI = 1.30-2.09) more vitamin D deficiency compared with mild cases. A vitamin D concentration insufficiency increased hospitalization (OR = 1.81, 95% CI = 1.41-2.21) and mortality from COVID-19 (OR = 1.82, 95% CI = 1.06-2.58). We observed a positive association between vitamin D deficiency and the severity of the disease.